2014
DOI: 10.5667/tang.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and antioxidant activity of Leea asiatica leaves against acetaminophen-induced hepatotoxicity in rats

Abstract: Leea asiatica (L.) Ridsdale, a folk medicinal plant is used by the ethnic people of North East India for the treatment of hepatic disorder. In this study, we have investigated the hepatoprotective and antioxidant activity of L. asiatica leaves against acetaminophen induced hepatotoxicity. Methanol extract of L. asiatica (150 and 300 mg/kg/day, p.o.) were administered to rats for three consecutive days followed by single acetaminophen (3000 mg/kg, p.o.) administration on 3 rd day. After 48 h of acetaminophen ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Thus, this study supports the evidence for clarifying the anthelmintic effect of L. asiatica . The antioxidant properties of the L. asiatica extract were well-proven in previous literatures and, especially the ethyl acetate-soluble extract, showed the most potent antioxidative effects [16]. In this study, eight flavonoids ( 9 – 16 ) were determined specifically from the ethyl acetate-soluble extract (Supplementary Information SI 9), which indicated that flavonoids were enriched in an ethyl acetate-soluble extract.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…Thus, this study supports the evidence for clarifying the anthelmintic effect of L. asiatica . The antioxidant properties of the L. asiatica extract were well-proven in previous literatures and, especially the ethyl acetate-soluble extract, showed the most potent antioxidative effects [16]. In this study, eight flavonoids ( 9 – 16 ) were determined specifically from the ethyl acetate-soluble extract (Supplementary Information SI 9), which indicated that flavonoids were enriched in an ethyl acetate-soluble extract.…”
Section: Resultssupporting
confidence: 56%
“…As mentioned in the Introduction, L. asiatica possessed anthelmintic [14] and antioxidative activity-related nephroprotective and hepatoprotective effects [15,16]. The current study demonstrated the presence of triterpenoids, including oleanolic acid, ursolic acid, the representative pentacyclic triterpenes, and their derivatives ( 1 – 8 ).…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Overdose APAP overwhelms the hepatic detoxification process and depletes GSH, which leads to oxidative stress and further contributes to liver injury [28]. Therefore, antioxidants and antioxidant-rich plant may be used as therapeutic agents for liver damage [27, 29, 30]. An increasing body of evidences have proved that alleviating oxidative stress and inflammation would be a potential way to attenuate acute liver injury induced by APAP [3133].…”
Section: Introductionmentioning
confidence: 99%